2023
DOI: 10.1007/s41042-023-00097-3
|View full text |Cite
|
Sign up to set email alerts
|

Character Strengths as Moderators of the Relationship Between Adverse Childhood Experiences and Negative Health Outcomes

Abstract: Adverse childhood experiences (ACEs) refer to negative events of childhood. Research has demonstrated relationships between ACEs and adult mental and physical difficulties. Fewer studies have examined potential moderators of these relationships. This study assessed the role of character strengths in the relationship between ACEs and negative physical and mental health outcomes in adulthood. An online sample of 1,491 adults completed questionnaires measuring character strengths, exposure to ACEs, and aspects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
1
2
0
Order By: Relevance
“….11) is also not particularly easy to detect when only considering variable importances (again, with the same exception as in the example above). Irrespective of culture, we could replicate the finding that not all character strengths have (normative) positive effects on the outcomes (e.g., Wallace et al, 2023), for example we found that (when controlled for all other strengths) higher values in Appreciation of Beauty, Kindness or Spirituality were associated with a higher number of days the participants felt worried, tense or anxious, sad, blue or depressed, or reported insufficient sleep.…”
Section: Cross-cultural Examination Of Character Strengths' Predictiv...supporting
confidence: 58%
See 1 more Smart Citation
“….11) is also not particularly easy to detect when only considering variable importances (again, with the same exception as in the example above). Irrespective of culture, we could replicate the finding that not all character strengths have (normative) positive effects on the outcomes (e.g., Wallace et al, 2023), for example we found that (when controlled for all other strengths) higher values in Appreciation of Beauty, Kindness or Spirituality were associated with a higher number of days the participants felt worried, tense or anxious, sad, blue or depressed, or reported insufficient sleep.…”
Section: Cross-cultural Examination Of Character Strengths' Predictiv...supporting
confidence: 58%
“…First, most studies of the relationship between characters strengths and measures of well-being focused on individual correlations, all of which tend to be positive (Par et al, 2004). More recently, Weziak-Bialowolska et al (2023) and Wallace et al (2023) used multiple regression analyses that included all 24 character strengths as simultaneous predictors of health-related variables. In both studies, Zest, Self-Regulation, Hope, and Gratitude had the largest positive associations with health.…”
Section: Character Strengths As Universal Predictors Of Health? Using...mentioning
confidence: 99%
“…Future studies might want to include variables that more directly tap into mortality risk in participants such as personal misuse of drugs or suicidal ideation. That said, there is some research suggesting many visitors to the VIA Institute website are at risk for despair, in that prior studies administering depression questionnaires to research volunteers on the site report that the mean score is indicative of some depression [ 39 , 40 ]. Though it is a question for which the current data provide no answer, it is possible that individuals seeking self-knowledge are a reasonable source of data for studying some aspects of deaths of despair.…”
Section: Discussionmentioning
confidence: 99%